Fine-Grained FeCoNi(CuAl)x High Entropy Alloys: Phase Transformation, Microstructure Evolution and Mechanical Properties - Long, Yan; Li, Guiqi; Liang, Xiaobiao; Peng, Haiyan (Frontiers in Materials, 2020)
A series of fine-grained FeCoNi(CuAl)x (x=0, 0.4, 0.6, 0.8, 1.0) medium-entropy alloy (MEA) and high-entropy alloys (HEAs) were fabricated by Mechanical Alloying (MA) and Spark Plasma Sintering (SPS). The effect of Al and Cu content (x) on phase composition, microstructure and mechanical properties of the alloys was investigated. Experimental results show that the crystal structure of FeCoNi(CuAl)x alloy transforms from single FCC phase for x=0 to FCC+BCC duplex phases for x=0.4~1.0, with the fraction of BCC phase gradually increasing with the increase of x. Adding a low content of Al and Cu elements to FeCoNi alloy can significantly hinder the grain growth during sintering process, the average grain size of FCC phase decreases from 0.95 to 0.30 µm at x=0.4. However, the grain sizes of FCC and BCC phases gradually grow up when x increases from 0.4 to 1.0. The variation in grain size indicates that the atomic diffusion rate of sintered alloy may be influenced by the sluggish diffusion effect in HEA as well as the content of Al and Cu with lower melting points. Mechanical properties of the HEAs are mainly affected by the volume fraction of BCC phase. The compressive yield strength and hardness of HEAs are improved at first and then slightly reduced, while the plasticity drops down continuously with the increase of x. The bulky HEA achieved excellent comprehensive mechanical properties with a compressive yield strength of 1467.7 MPa and plastic strain to failure of 24.9 % at x=0.6, due to the fine duplex microstructure.